PENGARUH KUALITAS PRODUK,PROMOSI DAN LAYANAN PURNA JUAL TERHADAP KEPUTUSAN PEMBELIAN MOBIL TOYOTA RUSH (STUDI KASUS DI NASMOCO PEMUDA SEMARANG) - Nurul Ayuningtyas; Handoyo Djoko Waluyo; Sari Listyorini (Universitas Diponegoro, 2015)
The research was motivated by the increasing of competition among automotive industries. From many types of car, Multi Purpose Vehicle/MPV is a favorite car in consumer. Toyota is one of vehicle producer which well known in Indonesia. Nowadays Toyota already produces a lot of type vehicle for middle economy. Toyota Rush is one of favorite vehicle for middle economy with affordable prices is the priority choice not only from the price but also from the function. The aim is this research is to know the impact of quality product, promotion, and after sales towards purchasing decision Toyota Rush. Type of this research is explanatory research. The collecting data method is using questionnaire. Sampling technique is purposive sampling. Sample in this research is 87 respondents from 677 populations. Likert scale is using for measurement. Linear regression analyze and path analyze are using to prove the hypotheses with SPSS 16.0 software. The research result showed that quality product variable (X1), promotion (X2) and after sales service (X3) have a positive and significant impact towards purchasing decision (Y). Based on this research, researcher suggest to Toyota Company to do more innovation and update application quality. For Nasmoco Pemuda as the official distributor in near future should give more satisfied after sales service to consumer, doing promotion, discount and lucky draw. It needed to increase the purchasing and compete with others automotive distributor.